2010
DOI: 10.1037/a0018531
|View full text |Cite
|
Sign up to set email alerts
|

Russian women émigrées in psychology: Informal Jewish networks.

Abstract: This paper uses archival sources and autobiographies to give a fuller account of the lives of three Russian women psychologists, each of whom voluntarily emigrated several years before the Third Reich. As such, their stories contribute to gender history, emigration history, and ethnic history. The characteristics of secondgeneration women in psychology seem to apply to this sample; they accepted applied or secondary positions in psychology or allied fields and came late to tenure-track positions. Some first-ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…The difficulty with using ethnicity as an explanatory factor in historical context is that it can mistakenly use the “one-drop rule” and a blood concept of Jewishness or any other ethnic identity. By this criterion, Koffka, whose “own mother Luise Levy was 'of Jewish descent' but became Protestant” (Woodward, 2010, p. 126), is a Jewish historical actor. Hans Eysenck and Arthur Jensen would also be included in this category, as well as Helmut Schmidt, at least two Nazi generals, and Nostradamus.…”
Section: Russians or Jews? Problems Of Jewish Identitymentioning
confidence: 99%
See 3 more Smart Citations
“…The difficulty with using ethnicity as an explanatory factor in historical context is that it can mistakenly use the “one-drop rule” and a blood concept of Jewishness or any other ethnic identity. By this criterion, Koffka, whose “own mother Luise Levy was 'of Jewish descent' but became Protestant” (Woodward, 2010, p. 126), is a Jewish historical actor. Hans Eysenck and Arthur Jensen would also be included in this category, as well as Helmut Schmidt, at least two Nazi generals, and Nostradamus.…”
Section: Russians or Jews? Problems Of Jewish Identitymentioning
confidence: 99%
“…As an allegedly permanent characteristic that cannot be shed by conversion, “Jewishness” is then readily available as an explanatory factor in all such cases. In Woodward's analysis, the complexities of Jewish identity are reduced to a simplistic dichotomy of “Just Jews” or “Jewish Jews,” borrowed from Freidenreich (Woodward, 2010, p. 130). The historically situated traditions of Reform Judaism, Orthodoxy, Hasidism, Zionism, Secular Judaism, and ethical culture, as well as the complex dynamics of conversion, identity concealment, intermarriage, and assimilation cannot be captured in this way.…”
Section: Russians or Jews? Problems Of Jewish Identitymentioning
confidence: 99%
See 2 more Smart Citations
“…These somewhat general and vaguely defined levels are covered by studies that can be viewed as providing an effective operationalization of the notion of the interdependency of ideas as informal personal networks of scholars, their friends and relatives, domestic and international peers, and the patrons of science (Adams 2001). A series of recent studies demonstrated the power of informal networks of agents as the social embodiment of the interdependency of ideas and practices in the world of Soviet music (Tomoff 2001), cybernetics and computer science (Gerovitch 2002; Tatarchenko 2010), biology and medicine (Krementsov 2005; Solomon 2006), and German-American psychology (Woodward 2010). …”
Section: Programmatic Conclusion: What Needs To Be Done and How?mentioning
confidence: 99%